Bibliophilos Books and Learning in the Byzantine World - Agoritsas, Dēmētrios K. ca. 20./21. Jh; Angold, Michael 1940-; Antonopoulos, Panagiotis; Bianconi, Daniele; Chrysos, Evangelos; Dendrinos, Charalambos; Easterling, Patricia; Giarenis, Ilias; Gioffreda, Anna; Ioannides, Archim. Gregorios A.; Kafasis, Christos; Magdalino, Paul; et al. (De Gruyter, 2021)
The present volume is a Festschrift in honour of the distinguished Byzantinist Costas N. Constantinides. The title of the volume, Bibliophilos: Books and Learning in the Byzantine World, reflects Professor Constantinides' major contribution to the fields of Greek palaeography, editions of Byzantine texts, Byzantine history, scholarship and education, and Cypriot manuscripts and culture. The volume is introduced by a preface and a tabula gratulatoria dedicated to the honorand, followed by twenty articles, written by seasoned and younger scholars, who are former colleagues and students of Professor Constantinides. These articles, which appear in alphabetical order, offer new material and shed fresh light to the study of Greek manuscripts, binders and scribes, and the life, works and activities of Byzantine scholars, teachers and students, providing editions of unpublished texts, including letters and poems, and exploring various aspects of Byzantine and Cypriot history, literature, art, science and culture. In the process the authors often challenge earlier views and offer new interpretations and insights. Bibliophilos is a book for the student, teacher and scholar of Byzantium in particular, and for every bibliophile in general
Description based on online resource; title from PDF title page (publisher's Web site, viewed 26. Mai 2021)
Keywords: Geschichte; Byzanz; Handschrift; Paläographie; HISTORY / Byzantine Empire; Lesekultur; Wissensvermittlung; Byzantinisches Reich; Festschrift